(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Urinary tract infection (UTI) remains one of the most common and major complications after renal transplantation. Objective: The study was undertaken to get an insight regarding the bacterial pathogen which is responsible for UTI in post renal transplant patients and their risk factors association. Methods: This was an observational study, conducted in the Department of Microbiology and Immunology Bangabandhu Sheikh Mujib Medical University (BSMMU) from December 2010 to December 2011. Twenty- one renal transplant recipients were evaluated for UTl after surgery up to six weeks. Microscopic examination and culture of urine were performed in every pre-transplant period, 3rd POD, 7th POD, within six weeks and as per patient’s clinical condition. UTI was considered when bacterial count was